ANALISIS TOTAL BAKTERI COLIFORM FECAL DAN NON FECAL PADA SAMPEL AIR SUMUR BOR DI WILAYAH TUNTUNGAN II DENGAN METODE TABUNG GANDA - Willis Pasaribu, Nadhilah; Amelia Nasution, Rizki (Universitas Cokroaminoto Palopo, 2025)
Increasing awareness of the importance of sustainable agriculture encourages the use of local resources, including organic tofu waste and ecoenzyme as alternative nutrient sources in the cultivation of red spinach (Amaranthus tricolor L.) in a hydroponic system. Ecoenzyme is a result of fermentation of household organic waste, has the potential to increase the efficiency of nutrient absorption and plant growth. This research method uses a non-factorial randomized block design with 4 treatments and 5 repetitions. The first treatment as a control consisted of AB mix 10 ml/liter of water, the second treatment (450 ml POC/liter of water), the third treatment (1 ml ecoenzyme/liter of water) and the fourth treatment (45% POC and 1 ml ecoenzyme/liter of water). The duration of the study was 1 month since transplanting. The parameters measured included plant height, number of leaves, leaf area, plant wet weight, root volume and chlorophyll content of red spinach. The results showed that the combination of tofu waste POC and ecoenzyme gave significant results in increasing the growth of red spinach compared to other treatments. The conclusion of this study is that the best treatment is the fourth treatment, namely 45% POC and 1 ml of ecoenzyme/liter of water).